ADVANCED MANUFACTURING SYSTEMS AND ENTERPRISES: CLOUD AND UBIQUITOUS MANUFACTURING AND AN ARCHITECTURE - Putnik, Goran D (Journal of Applied Engineering Science, 2012)
In this paper, in the first part an introduction to development of the concepts of Ubiquitous and Cloud Manufacturing is presented, as a model of advanced manufacturing systems and enterprises. In the second part an architecture, that might guide the implementation and exploitation of the Ubiquitous and Cloud Manufacturing is presented through an informal and conceptual presentation.Key words: Ubiquitous Manufacturing. Cloud Manufacturing, Manufacturing System, Architecture,Service Systems, Paradigm
Keywords: Paradigm; Enterprises; Ubiquitous; Manufacturing Systems; Clouds; Architecture